Balclutha jafara (Hemiptera: Cicadellidae): integrative identification of a species introduced in the Western Hemisphere, and notes on other Balclutha - Zahniser, James N.; Halbert, Susan E.; Moore, Matthew R.; Mottern, Jason L.; Beuzelin, Julien M. (Zootaxa, 2023)
Leafhopper specimens of the genus Balclutha Kirkaldy, found in southern Florida (Palm Beach and Collier Counties), United States, beginning in 2020, and in shipments of plant products originating from Colombia and entering the United States beginning in 2019, are identified as B. jafara Webb. This species was previously known only from the Seychelles and Aldabra Islands, which are parts of the Seychelles archipelago in the Indian Ocean east of mainland Africa. Identifications were made by comparison with type specimens, both morphologically and through molecular analysis. Specimens in Palm Beach Co. were swept from commercial rice (Oryza sativa L.) paddies. Mitochondrial cytochrome c oxidase I (COI) barcodes of specimens from Florida and Colombia were closely matched to each other and to partial barcodes obtained from paratype specimens of B. jafara. The COI barcodes also closely matched sequences from previously unidentified Balclutha specimens in the Barcode of Life Data Systems (BOLD) from Kenya and South Africa, several of which were confirmed later morphologically as B. jafara. Previously unidentified museum specimens from South Sudan, Zambia, and Zimbabwe were determined as B. jafara. Together, these specimens show that B. jafara has a more widespread African distribution than was known previously, and that it arrived in the Western Hemisphere by 2019. Balclutha jafara is redescribed and illustrated. Further studies on the Balclutha fauna of Florida were performed. COI barcode data were generated for Floridian specimens of B. caldwelli Blocker, B. curvata Caldwell, B. flavescens (Baker), B. frontalis (Ferrari), B. incisa (Matsumura), and B. lucida (Butler). A phylogenetic analysis of COI data was conducted using publicly available sequences and those generated here. A key to the Balclutha species known from Florida is provided. The names that have been applied and mis-applied to Western Hemisphere species are discussed. To clarify the identity of some species, illustrations are given for: the female holotype and a male paratype of Eugnathodus virescens Osborn (=B. flavescens); the holotype of Nesosteles robustus Caldwell (=B. robusta); and the holotype of Balclutha curvata Caldwell. Additional barcoded specimens of Balclutha from Kenya and Pakistan were provided for examination by the BOLD research group and determined as B. sujawalensis Ahmed, previously known only from India and Pakistan, and this species is also illustrated here.